THE EXPERIENCE OF MEDICAL VISIT COMPANIONS ACCOMPANYING OLDER ADULTS TO PHYSICIAN VISITS. (11th November 2018) - Sheehan, O; Blinka, M; Phillips, A; Roth, D
Abstract: Only 37% of older adults routinely attend doctor visits with a companion and most of these are spouses of the patient. However, other family members, close friends or community volunteers may also serve in this role. Some companions provide only transportation or companionship, but many others act as patient advocates, collateral informants, and coordination facilitators. We conducted focus groups of different types of Medical Visit Companions (MVCs) focusing on non-spouse and volunteer MVCs who were recruited through faith-based (n=50) or community organizations (n=15). Qualitative inductive analysis was used to organize thematic content. MVCs described their experiences positively but also highlighted many challenges related to the role including scheduling, transportation, communication, and coordination of care expectations. Companions played many roles before and after the visit and not just during the healthcare encounter itself. Although many volunteer MVCs only provided transport, others played active roles during the visit and engaged in care coordination. Our increasingly complex healthcare system can be especially challenging for older adults to navigate successfully. This work highlights the many benefits of having a companion accompany older patients to medical visits. Older adults without companions are particularly vulnerable and this gap may be filled by community volunteers. Further study is needed to see how volunteer MVCs from outside of one's family can best contribute to improved patient-centered care for older patients.